(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Prior eccentric or eccentric-concentric exercise induces long lasting muscle fatigue and delayed onset muscle soreness (DOMS). Moreover, the surface electromyograme sEMG amplitude increases under fatigue conditions. We suppose that prior eccentric – concentric exercise, inducing DOMS, increases EMG amplitude of thigh muscles during constant cycling exercises. Research aim of the study was to assess the residual effect of 100 prior drop jumps (PDJ) on the sEMG of m. vastus lateralis and m. vastus medialis during moderate and heavy intensity cycling exercises. Research methods. On four different days 10 female students performed one increasing and three (control, 45 min and 24 h after 100 drop jumps) moderate and heavy cycling (Ergoline-800, Germany) exercises. The cadence of cycling was 70 rpm. The sEMG of right thigh m. vastus lateralis and m. vastus medialis were continuously recorded during moderate and heavy cycling exercise. Creatine kinasis activity was measured and DOMS was rated 24 h after PDJ. Research results. After 24 h the subjects felt moderate DOMS (5.0 (2.79)) according to 10 point scale. The sEMG root mean square amplitude of m. vastus lateralis significantly increased 24 h after PDJ during moderate, but unaltered during heavy cycling exercise under fatigue conditions (45 min and 24 h after PDJ). Discussion and conclusion. Prior drop jumps seem to have significant residual (within 24 h of recovery) effect on EMG of thigh muscles during moderate cycling exercise in female students. Keywords: delayed onset muscle soreness, constant load, EMG root mean square.